Assessing the biodiversity value of degraded lowland forest in Sumatra, Indonesia - William Marthy; Yann Clough; Teja Tscharntke (KUKILA, 2016)
Forest degradation, forest fires, and wildlife poaching have devastated biodiversity in Indonesia. To assess the impact of forest degradation and the potential for recovery, we used birds as a proxy for biodiversity and assessed density estimates (hereafter density) in the degraded lowland forest of Harapan Rainforest Ecosystem Restoration Concession (HRF) in Sumatra. In this study, a total of 149 bird species (from 5,317 individuals) were recorded. Of the 103 species for which densities could be calculated, 45% were lowland bird specialists (i.e. species occurring below 200 m above sea level in Sumatra), including three globally threatened and 41 Near-Threatened species. Comparison with bird densities in degraded forest of Borneo revealed that there was broad similarity across taxa but three species had significantly higher density, and four had significantly lower density, in HRF. The mosaic of degraded forest habitats in different stages of regeneration in HRF appears to support more individuals of some species, especially woodpeckers, than the Bornean sites, but fewer individuals of other species. Determining bird densities is essential to establish population baselines, allowing comparisons between sites and over time. The present study fills one gap, but we urge others to conduct similar studies to provide a better understanding of the temporal and spatial variation in bird density in Southeast Asia’s degraded forests.